Prevalence and factors associated with undernutrition among children under the age of five years in Benin. - Isaac Yeboah Addo; Elijah Frimpong Boadu; Emmanuel Osei Bonsu; Caleb Boadi; Frederick Asankom Dadzie (PLoS ONE, 2023)
Background Benin ranks as one of the countries in the world with an alarmingly high prevalence of stunting, wasting, and underweight in children under five years. However, limited studies have examined the factors associated with the prevalence of these undernutrition indicators among children under five years in the country. This study aimed to fill this research gap by examining the prevalence rates and factors associated with stunting, wasting, and underweight among this specific population of interest. Methods This quantitative study utilised data from the most recent Benin Demographic and Health Survey (BDHS) conducted in 2017-18. The survey employed a nationally representative cross-sectional design and utilised a two-stage stratified cluster sampling technique to select participants. The study included a sample of 13,589 children under the age of five years. The main analytical approach employed was binary logistic regression, which was used to explore the associations between undernutrition (the combined outcome variable representing stunting, wasting, and underweight) and various socio-demographic factors. Results The combined prevalence of stunting, wasting, and underweight among children under five years in Benin during the 2017-18 survey period was 14.95%. Several factors were significantly associated with these indicators of undernutrition, including female gender (AOR = 0.71, 95% CI = 0.59-0.85), birth weight of 4.1 kg and over (AOR = 0.26, 95% CI = 0.14-0.48), multiple births (AOR = 3.22, 95% CI = 2.11-4.91), and a child's experience of diarrhoea (AOR = 1.76, 95% CI = 1.40-2.20). Furthermore, the prevalence of these undernutrition indicators was higher among children whose mothers had lower levels of education (AOR = 0.82, 95% CI = 0.01-0.42) and were unmarried (AOR = 0.67, 95% CI = 0.49-0.93). Conclusions This present study confirms that undernutrition rates are elevated in Benin and are closely linked to perinatal factors such as birth weights and multiple births, postnatal health conditions including diarrheal episodes, and socio-demographic determinants such as a child's gender, maternal education level, and marital status. Therefore, there is the need to consider specific modifiable factors, such as low birth weight, episodes of child diarrhoea, and maternal education as priority targets for child nutrition interventions in Benin.